Una experiencia universitaria innovadora: la odontopediatría durante la pandemia de COVID-19 - Carletto Körber, Fabiana Pía Marina (2022)
The reality imposed by the health emergency and the impact that SARS-CoV-2 has on humanity posed a fundamental challenge in the Pediatric Dentistry course to continue educating. Our objective was to have the necessary means to strengthen continuous innovation in use of methodologies and information and communication tools that would allow us to fulfill our commitments to the students. The course structure consisted of theoretical classes, lectures, and practical work applying the theory. The didactic proposal focuses on the child as a bio-psycho-social unit in constant evolution that must be approached in an integral and interdisciplinary manner, taking into account the social context. All teaching instances were developing the virtual modality. The pandemic situation posed several challenges, which we could successfully address. The educational continuity during the first phase of the pandemic was result of the creativity, innovation, and adaptation shown by both teachers and students.